2022
DOI: 10.15407/cryo32.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability in Cryoresistance of Saanen Goats Spermatozoa and Reproductive Characteristics

Abstract: Cryopreservation of gametes is one of the important stages of assisted reproductive technologies (ART). To obtain high results using ART, it is essential to cryopreserve sperm in a favorable season, when gametes have a high ability to fertilize oocytes. The aim of this research was to study seasonal variability of spermatozoa cryoresistance and reproductive characteristics of Saanen goats. After removing the seminal fluid, the gametes of five mature animals were cryopreserved in a solution of 10% glycerol and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…To ensure a high fertilization rate after cryopreservation, spermatozoa must have a high cryotolerance. Our previous studies have shown that to achieve higher fertilization rate using cryopreserved sperm of Saanen goats, it is recommended to collect semen during the breeding season [2]. In general, sperm resistance to cryodamage is associated with seminal plasma proteins that provide protection against oxidative stress during cryopreservation [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To ensure a high fertilization rate after cryopreservation, spermatozoa must have a high cryotolerance. Our previous studies have shown that to achieve higher fertilization rate using cryopreserved sperm of Saanen goats, it is recommended to collect semen during the breeding season [2]. In general, sperm resistance to cryodamage is associated with seminal plasma proteins that provide protection against oxidative stress during cryopreservation [18].…”
Section: Resultsmentioning
confidence: 99%
“…А. О. Богданюк 1,2 , В. В. Гаркавий 3 , М. П. Петрушко 1 baa1995ua@gmail.com 1 Інститут проблем кріобіології і кріомедицини НАН України, вул. Переяславська, 23, м. Харків, 61016, Україна 2 ТОВ «Інститут Сучасних Ветеринарних Технологій», вул.…”
Section: репродуктивні характеристики цапів зааненської та альпійсько...unclassified